The Temporal-Based Forest Disturbance Monitoring Analysis: A Case Study of Nature Reserves of Hainan Island of China From 1987 to 2020 - Xiao, Han; Zhang, Xiaoqian; Yan, Min; Zhang, Li; Wang, Hua; Ma, Yan; Liu, Jianbo (Frontiers in Environmental Science, 2022)
The Span of Forest Disturbance Monitoring can provide scientific data basis for decision-making. LandTrendr algorithm has been used to carry out appropriated segmentation and linear fitting to identify disturbance changes in timescale. The data of Sentinel and Worldview satellites are integrated to verify the accuracy of disturbance analyses in the context of ground truth data. The multifaceted forest vegetation disturbance changes analysis from 1987 to 2020 is obtained based on 23 Hainan Island Nature Reserves. Our demonstrated results are illustrated as following: (1) The total disturbed forest area in Hainan National Nature Reserve was 160.14km2 in the past 33 years in terms of an average disturbed forest area of 4.85km2 annually. (2) Local nature reserves were the most disturbed category with a total area of 131.75 km2 on the aspects of multiple nature reserves with a total area of 28.39 km2. (3) Forest ecological nature reserves is the largest (102.96km2), secondly marine coastal nature reserves (36.99km2), wild animal nature reserves (10.22km2) and the least wild plant nature reserves (9.96 km2); (4) Most disturbances are occurred in the 1990s and the early 21st century. (5) Forest vegetation area in the coastal nature reserve was larger than the inner of Hainan Island.